The Entry of Low-Cost Airlines: Price Competition in the European Airline Market - Marco Alderighi; Alessandro Cento; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2004)
This paper investigates the response of full service carriers (FSCs) to theentry of low-cost carriers (LCCs). We develop a model of airlinecompetition, which accommodates various market structures, some ofwhich include low-cost players. Using data on published airfares ofLufthansa, British Airways, Alitalia and KLM for the main city-pairs fromItaly to the rest of Europe, our statistical modelling resu1ts confirm theconclusions of the theoretical model. Competition among FSCs appears toaffect the price levels of business and leisure segments asymmetrically. Incontrast, competition with LCCs reduces the fares of FSCs in all classesproportionally.
Keywords: D43; L15; L93; 330; Pricing strategies; yield management; low-cost carriers; European airline market; Luftverkehr; Markteintritt; Preiswettbewerb; Europa; Revenue-Management